Satire as Tool of Political Cartoons in the Nigerian National Dailies: A Critical Discourse Analysis - Salisu Ogbo, Usman; Nuhu, MomohTairu (European Scientific Journal, ESJ, 2016)
This work is an analysis of the use of satire as a form of imagery to depict some political issues in cartoons as featured in the Nigerian national dailies. Survey method of research design was adopted as a means of sampling copies of national dailies from which political cartoons were selected, while Critical Discourse Analysis (CDA) was adopted for the analysis of data gathered. Findings reveal images of corruption, official responsibility, political failure and brutality/cruelty/suffering as the dominant concerns of the cartoons featured by the papers. While the corrupt postures of those who have links with the past government are dominant in the image of corruption portrayed, both those in and out of government are subjected to some satiric expose in respect of official responsibility, failure in politics and brutality/cruelty/suffering. At the end, it is recommended, among others, that more searchlight should be focused on the corrupt tendency of those still in power, and that more research efforts be devoted to the use of political cartoons to encourage citizen participation in national discourse.